1997
DOI: 10.1088/0034-4885/60/5/002
|View full text |Cite
|
Sign up to set email alerts
|

Theory of semiconductor surface reconstruction

Abstract: We present a review of semiconductor surface reconstruction. Experimental and theoretical results on atomic geometry, electronic states, phonon modes, and bonding are presented for clean cleaved, clean epitaxially grown, overlayer covered, surfactant mediated epitaxially grown, and defect induced reconstructed semiconductor surfaces. Energetic aspects of reconstructions are discussed using empirical as well as first-principles theoretical approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
65
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(69 citation statements)
references
References 272 publications
(448 reference statements)
3
65
0
1
Order By: Relevance
“…They have also served as mechanisms for molecular repositioning [9,10] and selective cleavage of molecular bonds [11]. They have been used to investigate reconstruction of semiconductor surfaces upon cleavage, epitaxial growth, annealing, deposition of surfactant layers, even controlled manipulation of individual atoms [12]. These kinds of investigations have not been widely applied in structural biology because of the fragile character of the materials and their liquid environments.…”
Section: Introductionmentioning
confidence: 99%
“…They have also served as mechanisms for molecular repositioning [9,10] and selective cleavage of molecular bonds [11]. They have been used to investigate reconstruction of semiconductor surfaces upon cleavage, epitaxial growth, annealing, deposition of surfactant layers, even controlled manipulation of individual atoms [12]. These kinds of investigations have not been widely applied in structural biology because of the fragile character of the materials and their liquid environments.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] In contrast to the anion vacancy, there are only a few studies of cation vacancies. In scanning tunneling microscopy ͑STM͒ images of the unoccupied states of GaAs ͑110͒ surfaces, two features interpreted as being caused by Ga vacancies have been reported: Lengel et al 7 observed a dark contrast that appears on an array consisting of about 3 ϫ 3 missing unoccupied dangling bonds, whereas Ebert and Urban 8 and Domke et al 9 observed an X-shaped dark contrast consisting of one missing unoccupied dangling bond.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the high energetic cost related to dangling-bond formation, semiconductor surfaces tend to display major reconstructions, 5 where the atomic arrangement in the outermost layers strongly differs from the bulk crystal one. As a consequence, growth modeling gets particularly challenging: newly deposited atoms might not find epitaxial sites directly at the surface, and further evolution could be needed before the reconstruction can be rebuilt.…”
Section: Introductionmentioning
confidence: 99%